2018
DOI: 10.3390/inorganics6020050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of (pyNO−)2GaCl: A Redox-Active Gallium Complex

Abstract: Abstract:We report the synthesis of a gallium complex incorporating redox-active pyridyl nitroxide ligands. The (pyNO − ) 2 GaCl complex was prepared in 85% yield via a salt metathesis route and was characterized by 1 H and 13 C NMR spectroscopies, X-ray diffraction, and theory. UV-Vis absorption spectroscopy and electrochemistry were used to access the optical and electrochemical properties of the complex, respectively. Our discussion focuses primarily on a comparison of the gallium complex to the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Even after the purge of a reductant iodide, the electron-accepting trifluoromethyl group facilitates the reduction of the nitroxide group. The redox ability of the tert-butyl pyridyl nitroxides has been well investigated [161][162][163][164][165] and actually confirmed here. Charge-transfer-triggered switching materials, like valencetautomeric cobalt(II)-SQ compounds [71][72][73] would be a next target of interest.…”
Section: Miscellaneoussupporting
confidence: 79%
See 2 more Smart Citations
“…Even after the purge of a reductant iodide, the electron-accepting trifluoromethyl group facilitates the reduction of the nitroxide group. The redox ability of the tert-butyl pyridyl nitroxides has been well investigated [161][162][163][164][165] and actually confirmed here. Charge-transfer-triggered switching materials, like valencetautomeric cobalt(II)-SQ compounds [71][72][73] would be a next target of interest.…”
Section: Miscellaneoussupporting
confidence: 79%
“…We [74]) but very close to that of aminoxylates (1.40-1.42 Å [161][162][163][164][165]). Consequently, the present compounds can be assigned to a reduced form (i.e., phpyNO -).…”
Section: Miscellaneoussupporting
confidence: 63%
See 1 more Smart Citation
“…Evaluation of redox reaction between gallium-indium-stannum alloy and redox active species showed that Ga was more easily oxidized by losing electrons than other metals [ 22 ]. When Ga was coordinated with a redox-active ligand, it was able to regulate the electronic nature of the ligand [ 23 ]. 67 Ga (half life 78 h) and 68 Ga (half life 68 min) has been successfully used as imaging agents to assess certain types of tumors, inflammation, and other lesions [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%